Nutrition for travel - Reilly, T.; Waterhouse, J.; Burke, L. M.; Alonso, J. M. (Journal of Sports Sciences, 2007)
The training and competitive programmes of elite athletes incorporate travel schedules, often long journeys, across multiple time zones. In such cases, travel causes both transient fatigue and a malaise known as "jet-lag" that persists for some days. Jet-lag is due to the disturbance of the body's circadian rhythms: diurnal and performance rhythms are displaced, depending on the direction of travel and the number of time zones crossed in flight. Attention to diet and hydration is relevant during the flight and following disembarkation until adjustment to the new meridian is complete. The consequences of jet-lag on rhythms in digestion may be compounded if food preparation and hygiene are inadequate in training camps or competitive venues overseas. The irony of travel is that it often places athletes at a greater risk of failing to meet their specific nutrition goals or succumbing to illness, at a time when the demands or outcomes of performance are of greatest importance. In addition, gastrointestinal infections related to travelling are frequent among athletes. Fastidious planning and organization among the support staff is recommended before the journey to prevent any such problems arising. Equally, athletes often need special education initiatives to assist them to cope with the challenges of a new and unusual food supply, or altered access to food.